Uredniška politika in formalne lastnosti razpravnih besedil Slavistične revije med letoma 1948 in 1977 - Bonšek, Uroš (Slavistična revija, 2008)
The article attempts to show the methodology of linguistic and literary scholarship in Slavistična revija between 1948 and 1977 and how (considering the practice of the current scholarly writing) the formal characteristics of its scholarly papers were changing. The author also examines the degree to which the articles in the journal in this thirty-year period follow the concept of the journal articulated in the first issue of volume I, and whether or not to what extent the concept of individual volumes and issues was unfluenced by the editorial policy (i.e., by the composition of the editorial board and/or by the editor-in-chief).
Keywords: 1948-1977; razprave; Slavic studies; Slavistična revija; slavistika; uredniška politika; znanstvene revije